SpecUnPy: A python GUI/App for neutron spectrum unfolding - Machado, Igor Andrade; García-Baonza, Roberto; de Sousa Lacerda, Marco Aurélio (Applied radiation and isotopes, 2023)
Bonner Sphere Spectrometers (BSS) are widely used for neutron spectrometry. Spectra are obtained by unfolding detector readings. In this work, a Python Graphical User Interface Application (GUI/App) for spectrum unfolding is presented; SpecUnPy. In this App, the user can choose three unfolding algorithms: SPUNIT/MLEM/GRAVEL. There is no limit for energy bins or detectors and after unfolding, a “.xlsx” file and a graphical comparison can be downloaded. This paper presents SpecunPy and some tests performed to validate it. •A Python Graphical User Interface Application (GUI/App) for neutron spectrum unfolding is presented.•SpecUnPy App uses three unfolding algorithms: SPUNIT, MLEM, and GRAVEL.•The GUI/App was tested using data from IAEA compendium and EURADOS exercise.•SpecUnPy App is easy, friendly, intuitive, and reliably solves the neutron spectrum unfolding problem.